The effects of different saturation levels of the Shifting Boundaries intervention on preventing adolescent relationship abuse and sexual harassment - Taylor, Bruce G. (Journal of experimental criminology, 2017)
Prior research with the Shifting Boundaries (SB) prevention program suggests that it can prevent adolescent relationship abuse and sexual harassment. We assessed the relative impact of a combined set of SB classroom (SBC) and SB building (school-wide; SBS) interventions on adolescent relationship abuse and sexual harassment outcomes when the program is delivered to all three grades in a middle school (full saturation) compared to when only two or one of the three grades receive it.